Mouse fat storage‐inducing transmembrane protein 2 (FIT2) promotes lipid droplet accumulation in plants. Issue 7 (18th January 2017) - Cai, Yingqi; McClinchie, Elizabeth; Price, Ann; Nguyen, Thuy N.; Gidda, Satinder K.; Watt, Samantha C.; Yurchenko, Olga; Park, Sunjung; Sturtevant, Drew; Mullen, Robert T.; Dyer, John M.; Chapman, Kent D.
Summary: Fat storage‐inducing transmembrane protein 2 (FIT2) is an endoplasmic reticulum (ER)‐localized protein that plays an important role in lipid droplet (LD) formation in animal cells. However, no obvious homologue of FIT2 is found in plants. Here, we tested the function of FIT2 in plant cells by ectopically expressing mouse ( Mus musculus ) FIT2 in Nicotiana tabacum suspension‐cultured cells, Nicotiana benthamiana leaves and Arabidopsis thaliana plants. Confocal microscopy indicated that the expression of FIT2 dramatically increased the number and size of LDs in leaves of N. benthamiana and Arabidopsis, and lipidomics analysis and mass spectrometry imaging confirmed the accumulation of neutral lipids in leaves. FIT2 also increased seed oil content by ~13% in some stable, overexpressing lines of Arabidopsis . When expressed transiently in leaves of N. benthamiana or suspension cells of N. tabacum, FIT2 localized specifically to the ER and was often concentrated at certain regions of the ER that resembled ER‐LD junction sites. FIT2 also colocalized at the ER with other proteins known to be involved in triacylglycerol biosynthesis or LD formation in plants, but not with ER resident proteins involved in electron transfer or ER‐vesicle exit sites. Collectively, these results demonstrate that mouse FIT2 promotes LD accumulation in plants, a surprising functional conservation in the context of a plant cell given the apparent lack of FIT2 homologues in higher plants. These results suggest also that FIT2 expression represents an effective synthetic biology strategy for elaborating neutral lipid compartments in plant tissues for potential biofuel or bioproduct purposes.